Age-related productivity decrease in high-waged and low-waged employees. Issue 6 (2nd September 2019) - Roosaar, Liis; Masso, Jaan; Varblane, Urmas
Abstract : Purpose: The purpose of this paper is to clarify whether the age-productivity curve is different for low-waged and high-waged employees. Design/methodology/approach: Productivity growth is decomposed at the firm level into contributions by hired, separated and staying workers. Based on a matched employer-employee database of Estonian firms from 2006 to 2014 and considering the age as well as wages of employees, a panel data model with fixed effects is constructed to show the relative productivity of each cohort of employees. Findings: High-waged employees appeared to be relatively more productive than low-waged employees and middle-aged were more productive than young or old employees. However, the productivity difference between young and old employees was not statistically significant. The age-productivity curve of high-waged employees appeared to be flatter than that of low-waged employees. Only in knowledge intensive services were the low-waged old employees statistically significantly less productive than high-waged old employees. In the manufacturing industry, the young were more productive than in services, in knowledge intensive services the old were less productive than in traditional services. Research limitations/implications: The productivity of employees is only analysed for cohorts of employees. Practical implications: Employers can be encouraged to hire older employees because old employees are shown to remain at least as productive as young employees. Originality/value: The decomposition of labour productivity at the firm level is further developed, as the statistical difference between the productivity of different groups of employees is analysed.